Influence of Anykščiai city on Šventoji river water quality - Bagdžiūnaitė-Litvinaitienė, Lina; Litvinaitis, Andrius; Šaučiūnas, Laurynas (International Conference “Environmental Engineering”, 2017)
Increasing migration of nutrients in the river water is a major factor in determining the quality of river water due to anthropogenic activities. In order to preserve the good water quality in rivers and other surface water bodies, it is necessary to take preventive measures that can be scientific water quality research and analysis. According to research carried out in kind, the article analyses the Anykščiai city as point source pollution, and the influence of it to the water quality of Šventoji river. Also, based on the statistical information a nutrient concentrations trend analysis of the meteorological and hydrological conditions influence was carried out. Investigations were carried out in July-September of 2016. Concentrations of ammonium (NH4N), nitrite (NO2N), nitrate (NO3N), phosphate (PO4P) and dissolved oxygen (O2) was analysed. In order to determine the impact of point source pollution on river water quality, the changes in concentration before and beyond Anykščiai city were evaluated, according to the meteorological and hydrological conditions. It was found that total nitrogen (Nb) and total phosphorus (Pb) concentrations during the investigation period respectively, increases in 6% and 8%.